Management and Utilization of Productive Zakat in Improving the Musta?iq Economy at BAZNAS West Tanjung Jabung Regency - Novia Sumanti (Dinasti Publisher, 2022)
Which are the core of the activities of zakat management organizations are still a problem that occurs at BAZNAS, Tanjung Jabung Barat Regency. This study aims to determine how the management and utilization of productive zakat is carried out by BAZNAS in improving theeconomy musta?iq. This research is a qualitative research with the methods of collection and observation, interviews, and documentation. This study resulted in three conclusions, namely: 1) The mechanism of zakat management carried out by BAZNAS in Tanjung Jabung Barat Regency through activities of collecting and distributing zakat. For zakat collection, zakat is collected in two ways, through institutions collected by UPZ that have been formed and individually, namely the community paying their own zakat to BAZNAS. For the distribution of zakat, it is distributed according to what has been mandated in the Koran, namely given to eight groups. The form of distribution is consumptive in nature, that is, it is distributed in the form of cash or basic necessities and the distribution is productive in the form of business capital assistance, livestock hall programs and training for coaching SMEs in cake making. 2) The model of zakat utilization carried out by BAZNAS in Tanjung Jabung Barat Regency is productive and distributed in the form of the Qordhun Hasan program, the Livestock Center Program and the MSME Development of Cake Training. However, the utilization of productive zakat has not been maximized so that it still has not had an impact in terms of increasing the economy considering the implementation of the productive zakat program which is still just being implemented and there is no reporting of business development from musta?iqto BAZNAS. 3) Obstacles faced by BAZNAS in Tanjung Jabung Barat Regency in utilizing zakat, namely the collection of zakat funds has not been optimal so that it has an impact on the limited number of musta?iqand zakat funds received by musta?iq, limited human resources and the role of the government in supporting zakat management in the region is still not maximized.